Non-linear idealisation error analysis of an aerospace stiffened panel loaded in compression - Hetey, Laszlo; Campbell, James; Vignjevic, Rade (Sage, 2013)
The SAFE Structural Analysis procedure is an idealisation error control methodology devised for linear static finite element analysis. This study examines the applicability of this process to non-linear problems. The studied case is the collapse analysis of an aircraft stiffened panel loaded in compression. This article presents the critical investigation of important modelling assumptions, including the joint modelling, boundary conditions, geometrical imperfections and scattering in material parameters. Potential error sources are identified and then analysed using the non-linear finite element solver ABAQUS. The analysis derived an improved finite element model and concrete idealisation error estimates. The finally simulated failure behaviour corresponds well to the data measured in the test.
Keywords: Finite element method; error control; modelling; ABAQUS; non-linear; idealisation